Lamto GIS layer (raster dataset): vegetation cover of the Lamto reserve (Côte d'Ivoire) in 1988, after original map by Gautier (1990) - Zaiss, R.; Gignoux, J.; Barot, S.; Gautier, L.; Konaté, S. (DataSuds, 2022)
This dataset holds the map “Carte du recouvrement ligneux de la réserve de Lamto" published by Gautier, L. in 1990. We georeferenced the scanned paper map using ground control points derived from Google Maps. The dataset contains the scanned map, the ground control points and the raster layer of the georeferenced map.